Immunogenicity of the 13-Valent Pneumococcal Conjugate Vaccine in Older Adults With and Without Comorbidities in the Community-Acquired Pneumonia Immunization Trial in Adults (CAPiTA). (3rd July 2017) - van Deursen, Anna M M; van Houten, Marlies A; Webber, Chris; Patton, Michael; Scott, Daniel A; Patterson, Scott; Sidhu, Mohinder; Drews, Wayne; Gruber, William C; Emini, Emilio A; Grobbee, Diederick E; Bonten, Marc J M; et al.
Summary: In immunocompetent adults ≥65 years of age, 13-valent pneumococcal conjugate vaccine elicits significant increases in opsonophagocytic activity titers and IgG concentrations. Responses were sustained for 2 years postvaccination for subjects in each age stratum and comorbidity group. Abstract: Background: In the randomized controlled Community-Acquired Pneumonia Immunization Trial in Adults (CAPiTA), the efficacy of the 13-valent pneumococcal conjugate vaccine (PCV13) against first episodes of vaccine-type community-acquired pneumonia in adults aged ≥65 years was 46%. The long-term immunogenicity of PCV13 in pneumococcal vaccine–naive older adults was investigated as part of CAPiTA. Methods: We determined the immune responses to PCV13 before and at 1, 12, and 24 months after vaccination in 1006 PCV13 recipients and 1005 controls with 3 age-stratified study participant cohorts. PCV13 serotype-specific opsonophagocytic activity (OPA) titers and immunoglobulin G (IgG) concentrations were determined. Results: Sample collection completeness was at least 93.4% at each time point. In all 3 age categories, a single dose of PCV13 elicited OPA titers and IgG concentrations for all 13 serotypes that were significantly higher than baseline and the corresponding responses in the placebo group at all time points. In the eldest subjects (≥80 years of age at vaccination), OPA titers and IgG concentrations remained above baseline and there was no apparent difference in OPA titers and IgG concentrations between those with self-reported comorbidities and healthy older adults. However, the study was not powered to determine statistical significance between different age and comorbidity groups, and thus these results are exploratory. Conclusions: In immunocompetent adults ≥65 years of age, PCV13 elicits significant increases in OPA titers and IgG concentrations that persist 2 years postvaccination for all 13 serotypes, regardless of age and comorbidity. Clinical Trials Registration: NCT00744263